PENGEMBANGAN SISTEM INFORMASI APLIKASI SELF CHECK IN TERMINAL DOMESTIK DI BANDARA HALIM PERDANAKUSUMA (SAAT PANDEMI COVID 19) - Cynthia Rahmawati; Jehan Saptia Kurnia (Fakultas Ilmu Komputer dan Desain - Unsurya, 2021)
Based on the observations of researchers on September 23, 2020, there was a new enforcement in passenger check-in due to the covid 19 pandemic. The covid 19 pandemic resulted in the use of this application machine completely unusable. Passenger services use a new route, namely through 2 stages. Manual counters (Covid 19 health mail check counters and airline counters for boarding passes). The purpose of this study was to analyze and develop a self check-in application information system which during the Covid-19 pandemic had not been used optimally by passengers from airlines operating at the domestic terminal of Halim Perdanakusuma Airport. The approach method in developing this self-check-in application information system is the RAD (Rapid Application Development) method, namely the development team to create a fully functional system in a very short period of time. The results of the development of the information system for the self check in application are that it can develop an information system for passengers about basic knowledge of covid 19 and validation of covid 19 free health letters to be displayed in the self check in application at the domestic terminal at Halim Perdanakusuma Airport.Â Keywords: Development of System Informations, Self Check In, Domestic Terminal, Pandemi Covid 19, Halim Perdanakusuma Airport